Influence of Sultan Abdurrahman School of Health Technology Gwadabawa (SASHTG) on Girl–Child Education and Women Empowerment (Employment) in Gwadabawa, Sokoto State, Nigeria - Miya, Yusuf Yahaya; Arziki, Abubakar (EDUMALSYS Journal of Research in Education Management, 2024)
This study is to determine the positive influence of Sultan School of Health technology Gwadabawa, Sokoto, Nigeria on girl-child education and empowerment using a survey of 300 questionnaires drawn. The major The positive influence of SASHT on girl-child education as submitted by the respondents in order of frequency are: Giving opportunity to the girls/ women to obtain higher education (20.0%), Improvement in mother and child health, reduction in mortalities; by producing female health workers almost in every area or home in Gwadabawa (13.3%), Helps in providing employment to girls/ women (12.7%),Empowering girls/women when they are educated/ employed (10.0%), Better practice of personal/ environmental hygiene (10.0%),Influence girls/ women to be civilized (10.0%),Private practice (10.0%), and the least was Reduction of women scarcity at places of work (5.0%). The table 3 shows the challenges faced by girls/ women when studying at SASHT Gwadabawa in the order of descending score/percentage: Financial burden (50.0%), Requires high IQ (16.7%), Early marriage (16.7%), and Poor lower education (16.7%). The possible solutions to the challenges faced by girls/ women in studying health courses at SASHT were listed. The highest submitted option was giving scholarship to the girls/women (50.0%), creating awareness on the benefits of higher education (33.3%), and reduction of early marriage (16.7%). Indeed, the school is positively impacting on the girl-child education of Gwadabawa and the region (results of x2 show that there is significant difference at p<.05. Improvement in mother and child health, women empowerment, and opportunities for women/ girls to get employment are needed.